Southern Ocean deep convection as a driver of Antarctic warming events. Issue 5 (12th March 2016) - Pedro, J. B.; Martin, T.; Steig, E. J.; Jochum, M.; Park, W.; Rasmussen, S. O.
Abstract: Simulations with a free‐running coupled climate model show that heat release associated with Southern Ocean deep convection variability can drive centennial‐scale Antarctic temperature variations of up to 2.0°C. The mechanism involves three steps: Preconditioning : heat accumulates at depth in the Southern Ocean; Convection onset : wind and/or sea ice changes tip the buoyantly unstable system into the convective state; and Antarctic warming : fast sea ice‐albedo feedbacks (on annual‐decadal time scales) and slow Southern Ocean frontal and sea surface temperature adjustments to convective heat release (on multidecadal‐century time scales) drive an increase in atmospheric heat and moisture transport toward Antarctica. We discuss the potential of this mechanism to help drive and amplify climate variability as observed in Antarctic ice core records. Key Points: Southern Ocean deep convection events can explain up to 2.0°C warming in Antarctica Ocean adjustments to buoyancy loss causes an approximately 50 year lag in the Antarctic temperature response Southward atmospheric heat flux anomalies propagate the warming signal to Antarctica